The relationship of emotional intelligence, social intelligence, person-job fit, person-organization fit and empowerment to job performance at Putrajaya Immigration Department - Nur Izyan Izzati, Zazali (2019)
The purpose of this study is to investigate the relationship between emotional intelligence, social intelligence, person-job fit, person-organization fit and empowerment to job performance among employees of Putrajaya Immigration Department. The employees of Putrajaya Immigration Department was chosen as the respondents of this study. A total of seven research objectives were formulated. A questionnaire was adopted and adapted from previous related studies. The questionnaire was pilot tested before distributed to the target respondent. The respond rate was 98%. The descriptive, correlation and regression analysis was performed on the data. The results show that emotional intelligence, person-job fit, person-organization fit and empowerment is significant, positive with medium to low strength of relationship to job performance. Interestingly the social intelligence was not significant. The selection of independent variables can only explain 39.9% to job performance with emotional intelligence as the most influential variable. This is followed by empowerment and person-organization fit to explain the job performance among employees of Putrajaya Immigration Department. However, person-job fit and social intelligence have no influence on job performance. The Putrajaya Immigration Department is a government agency entrust with law enforcement activities. Therefore it is recommended to select other variables associated with law enforcement agency for future research.